Frequency and impact of regional musculoskeletal disorders. - Linaker, C; Walker-Bone, K; Palmer, K; Cooper, C (1999)
Regional musculoskeletal disorders are a major cause of morbidity both in the community and in the workplace. They comprise a heterogeneous group of conditions that are, for the most part, poorly characterized. Consequently, agreed diagnostic criteria have not existed for many of these disorders, and epidemiological investigations have used varied or ill-defined approaches to case definition. This chapter describes our current understanding of the epidemiology of regional pain disorders and details the strengths and weaknesses of the available data. Pain syndromes can be divided anatomically into those which cause generalized pain, such as fibromyalgia syndrome and myofascial pain syndromes, and those which are confined to one regional anatomical area. The latter group comprise those of the neck, shoulder, elbow, wrist/hand, hip, knee and ankle/foot. Current information is considered on the known risk factors for disorders at these sites, in addition to their impact upon both the individual and society.